CONTEMPORARY PROBLEMS OF ASTRONOMY: THE CHEMICAL COMPOSITION OF CEPHEIDS AND RELATED STARS - Andrievsky, S. M.; Klochkova, V. G. (Одеські астрономічні публікації, 2017)
In the short form we present the main results of spectroscopic analysis of the different kind of Cepheids and related stars: double-mode Cepheids, s-Cepheids, non-variable supergiants situated inside the Cepheids instability strip and Cepheids first time crossing the instability strip.